Sjögren Sensory Neuronopathy (Sjögren Ganglionopathy): Long-Term Outcome and Treatment Response in a Series of 13 Cases. Issue 19 (May 2016) - Pereira, P. Ricardo; Viala, Karine; Maisonobe, Thierry; Haroche, Julien; Mathian, Alexis; Hié, Miguel; Amoura, Zahir; Cohen Aubart, Fleur
Abstract : Abstract: Primary Sjögren syndrome (SS) is an autoimmune disease mainly affecting the exocrine glands causing a sicca syndrome . Neurological manifestations are rarely seen in SS although they are debilitating. Peripheral neuropathies namely sensory axonal neuropathy and painful small fiber neuropathy are the most frequent neurological manifestations. Sensory neuronopathy (SN) is less frequently seen although leading to more severe handicap. The aim of the study was to analyze the clinical presentation and treatment efficacy in a series of SS-related SN. We retrospectively studied patients with SS fulfilling the American–European Classification Criteria and SN according to recent criteria. Studied variables were neurological findings, associated autoimmune diseases, biological profiles, nerve conduction and sensory/motor amplitudes study, treatments received, and outcomes. Handicap scores were studied at beginning and end of each treatment using the modified Rankin Scale (mRS). Thirteen patients were included (12 women, 1 man; median age 55 years at SN diagnosis) presenting with SN with a median follow-up of 3 years (range 2–17). In 11 patients, SN preceded or coincided with SS diagnosis. Most common neurological findings were ataxia and areflexia followed by paresthesia and pain. Lower limbs were more affected than upper limbs, neurological deficits were often symmetric and cranial nerves were affected in 3 patients. Seven patients were treated with corticosteroids, 7 with mycophenolate mofetil, 6 with hydroxychloroquine, 5 with intravenous immunoglobulins, 4 with cyclophosphamide, and 2 patients received other immunosuppressive drugs. At the beginning and at the end of follow-up, average mRS was 2.15 (median 2) and 2.38 (median 2), respectively. SS-related SN progression is heterogeneous but tends to be chronic, insidious, and debilitating despite treatment. From these data concerning a small number of patients, treatment strategies with corticosteroids in association with immunosuppressive drugs, namely mycophenolate mofetil, had positive results. In contrast, intravenous immunoglobulins had disappointing results.